2022
DOI: 10.3390/vaccines10081304
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Deglycosylated Modified Hemagglutinin Broadly Protects against Influenza Virus Infection in Mice and Ferrets

Abstract: Recent efforts have been directed toward the development of universal influenza vaccines inducing broadly neutralizing antibodies to conserved antigenic supersites of Hemagglutinin (HA). Although several studies raise the importance of glycosylation in HA antigen design, whether this theory can be widely confirmed remains unclear; which influenza HA with an altered glycosylation profile could impact the amplitude and focus of the host immune response. Here, we evaluated the characteristics and efficacy of degl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Another concern with utilizing a viral vector for an LD vaccine is that the Bb proteins are glycosylated differently by Borrelia than when produced by mammalian cells, which is how a viral vector is developed. This could change the immune response to a bacterial protein induced by a viral vector [ 46 ]. In this study, we showed that the borrelial antigen BBI39 must be incorporated into the RABV virion to elicit high-titer anti-BBI39 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern with utilizing a viral vector for an LD vaccine is that the Bb proteins are glycosylated differently by Borrelia than when produced by mammalian cells, which is how a viral vector is developed. This could change the immune response to a bacterial protein induced by a viral vector [ 46 ]. In this study, we showed that the borrelial antigen BBI39 must be incorporated into the RABV virion to elicit high-titer anti-BBI39 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, in the case of surface proteins such as HA or NA, glycosylation may not keep pace with the high rate of their induced expression and deployment to the cell membrane or, possibly, the progeny virus envelope. A recent study demonstrated that an unglycosylated HA induced a broader protective response than the corresponding fully glycosylated HA [50].…”
Section: Discussionmentioning
confidence: 99%
“…Human viruses including influenza A virus (IAV) and SARS-CoV-2 use host-made glycans to facilitate infection and to shield the conserved epitopes on the virus surface from immune response. Vaccination with mono-glycosylated hemagglutinin (HA) or inactivated IAV-induced cross-strain protection against influenza virus infections ( 10 , 30 31 ). Interestingly, the HA stem-specific antibodies are broadly protective against most type A influenza viruses ( 32 , 33 ), and previous studies showed that deletion of the glycans in HA elicited a high level of stem-specific antibodies ( 34 37 ) and T cell response ( 37 ).…”
Section: Discussionmentioning
confidence: 99%